Clinical profile, risk factors and outcome of medical, surgical and adjunct interventions in patients with Pythiuminsidiosum keratitis. Issue 3 (11th September 2018) - Agarwal, Shweta; Iyer, Geetha; Srinivasan, Bhaskar; Benurwar, Saket; Agarwal, Mamta; Narayanan, Niveditha; Lakshmipathy, Meena; Radhika, N; Rajagopal, Rama; Krishnakumar, S; K, Lily Therese
Abstract : Purpose: To report clinical profile and compare management options for Pythium keratitis. Method: Retrospective interventional study of 46 patients diagnosed as Pythium keratitis by PCR DNA sequencing from January 2014 to July 2017. Interventions were categorised into medical management (MM) (topical azithromycin and linezolid with oral azithromycin at presentation), surgery (S) (therapeutic penetrating keratoplasty, TPK), surgical adjunct (SA) (cryotherapy±alcohol with TPK) and medical adjunct (MA) (MM after TPK). Results: Primary treatment included MM (1 eye), SA (3 eyes) and S (42 eyes). Recurrence occurred in 27/43 eyes (MM+S group). Second surgery (S) was required in 11 eyes (TPK-2), with additional procedures (SA) in 10 eyes and evisceration in five eyes. 8/43 eyes received MA after TPK-1. One eye required TPK-3. Recurrence occured in all eyes that received MA (100%) and in 28 of 54 TPKs (51.8%) (TPK 1+2+3) in 42 eyes. Recurrence was noted in 1/14 (7.1%) that underwent SA. Conclusion: The currently available and recommended treatment for Pythium keratitis is surgical by means of a TPK and in worse cases evisceration. In our study, MM/MA measures showed no benefit with recurrence or worsening of infection requiring resurgery. Almost 50% of TPKs had a recurrence requiring resurgery. However, adjunctive procedures during TPK appear to have additional benefit with low risk of recurrence and could be included as routine care.